PENGEMBANGAN MODUL AJAR SEJARAH RAPAT DAMAI TUMBANG ANOI 1894 DI SMKN 4 PALANGKA RAYA - Deva Oktavia Yuriana; Yudi Susanto; Sumiatie Sumiatie (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2026)
This study aims to develop a history teaching module on the 1894 Tumbang Anoi Peace Meeting that aligns with students’ characteristics and needs, assess its feasibility based on expert evaluations, and examine its effectiveness in enhancing historical awareness among eleventh-grade students at SMK Negeri 4 Palangka Raya. Using the Research and Development (R&D) method with a simplified Borg and Gall model and a contextual approach that connects local history with national history, the study involved observations, interviews, and validation tests conducted by subject matter, language, and media experts. The results indicate that the developed module is feasible for use and effectively improves students’ understanding of historical values, particularly those related to the struggles and local wisdom of the Dayak communit.